2017
DOI: 10.15537/smj.2017.2.15627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of software facilitated teaching on final grades of dental students in a dental morphology course

Abstract: Objectives:To evaluate differences in students’ performance in a dental morphology course after the introduction of a 3D software-teaching program.Methods:This retrospective study took place at the College of Dentistry, University of Dammam, Dammam, Kingdom of Saudi Arabia, from Augst 2013 to January 2016. The study included 3 groups of students taking the course during 3 different academic years: group 1, 2013-14 control; group 2, 2014-2015; and group 3, 2015-2016. The total sample size was 294 (n = 294; grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…In the present study, students who used interactive resources obtained better grades than those in the same class (Group B) who did not use them, although the difference was weak, particularly when one considers that there was a grade incentive. The final grade of these students was no better than that of those who did not have access to these interactive features (Group A), as previously observed 19,20 . The students themselves, in the present study, did not give a high score to the interactive resources available in the evaluation.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, students who used interactive resources obtained better grades than those in the same class (Group B) who did not use them, although the difference was weak, particularly when one considers that there was a grade incentive. The final grade of these students was no better than that of those who did not have access to these interactive features (Group A), as previously observed 19,20 . The students themselves, in the present study, did not give a high score to the interactive resources available in the evaluation.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast to the above study, another study compared one group of students who did not have access to the 3D Tooth Atlas nor was it used in class, to two other groups that received the software‐facilitated learning in each class period and were tested on the content present in the program. The study concluded there was a positive correlation between use of the software program and student performance in final examinations . Student perceptions of the program are shown in the post‐course survey results presented in Table .…”
Section: Discussionmentioning
confidence: 99%
“…Bogacki et al used equivalence testing to show that teaching of dental anatomy with an interactive computer program was found to be as effective as teaching with traditional lectures [ 11 ]. Whereas, Al-Thobity et al reported that students who received software-facilitated teaching performed better than the students who did not receive it [ 7 ]. Similarly, Nance et al evaluated the efficacy of a DVD demonstrating wax carving compared with traditional techniques.…”
Section: Challenging the Traditional Teaching Of Dental Anatomymentioning
confidence: 99%
“…Likewise, the course usually fails to prepare students to transition from pre-patient care to real clinical scenarios [ 5 ]. Moreover, the traditional lecture model presents several limitations, including one-way communication, lack of interaction, and poor student engagement [ 7 ]. Studying the theory of dental anatomy alone is not enough to acquaint students with the anatomy of each tooth in detail.…”
Section: Introductionmentioning
confidence: 99%